Queensland 1:25 000 series topographic map. 8456-1-SW. Macedon - Queensland. Department of Mapping and Surveying (Brisbane : Dept of Mapping and Surveying, 1977)
Cadastral information included.
Title on earlier sheets: "Queensland Australia 1:25 000 ; Queensland topographic survey".
Keywords: Macedon (Qld.) -- Maps